The effect of information overload and perceived risk on tourists’ intention to travel in the post-COVID-19 pandemic - Wu, Hong; Cao, Qi; Mao, Jia-Min; Hu, Hui-Ling (Frontiers in Psychology, 2022)
Since the COVID-19 pandemic, the tourism economy has been seriously hit. China has implemented a straight traveling management mechanism and recovered from this pandemic faster than the rest of the world. However, the COVID-19 situation still is complicated and uncontrollable. Especially, sorts of related information appeal involved medical professional knowledge and unfamiliar terminology. The main purpose of this empirical research is to understand the impact of the traveling intention of China tourists after the COVID-19 new normal. Along with information overload and perception risk, an expanded research model of the Theory of Reasoned Action (TRA) has been proposed. The research target is the tourists who spend their holiday in Hainan Province, a famous tourist destination in China. By conducting a survey, 250 valid samples were collected from three theme parks and several hotels. The empirical results show that information overload positively impacted perceived risk significantly. Perceived risk of traveling under COVID-19 pandemic negatively impacted traveling intention significantly. Also, perceived risk influenced traveling attitude negatively. However, response self-efficacy did not have a significant impact on traveling intention. Subjective norm did not have a significant moderating effect on the relationship between perceived risk and traveling intention. Overall, the results of this study strengthen deeply the understanding and prediction of the post-pandemic travel decision-making process of China tourists.